Tyrosinase-Based Paper Biosensor for Phenolics Measurement - Fretty Yurike; Dyah Iswantini; Henny Purwaningsih; Suminar Setiati Achmadi (Indonesian Journal of Chemistry, 2022)
Environmental pollution resulting from various industrial activities is still a problem for developing countries. The high content of phenolics such as phenols, polyphenols, bisphenol A, catechol, m- and p-cresol from industrial activities are discharged into surface water, soil, and air. Periodic monitoring of the impact of these toxic pollutants is needed for proper control and handling. These detrimental chemicals are usually measured using conventional methods with many drawbacks such as expensive analysis costs, long measurement times, requiring competent analysts, and complicated instrument maintenance. However, the presence of tyrosinase-based paper biosensors is now considered the most promising tool in overcoming the challenges mentioned earlier because they can detect these components quickly, precisely, accurately, inexpensively, and can be measured in situ. The working principle of this biosensor sees optical changes such as dyes, redox processes, and physicochemical properties (aggregation or dispersion) due to the presence of analytes accompanied by the occurrence of color changes that appear. This biosensor uses a layer-by-layer electrostatic method, which causes the deposition of multi-layered films on solid surfaces. In this paper, we review the development of the tyrosinase-based paper biosensor method for phenolic measurement in water, air, and food that gives better results than the conventional methods.